Pengelolaan Timbulan Sampah Untuk Menjaga Citra Industri Pariwisata Pada Daya Tarik Wisata di Bali - Kristina, Ni Made Rai; Darma, I Gusti Ketut Indra Pranata; Ratnaningtyas, Heny (Pusat Penelitian dan Pengabdian Kepada Masyarakat, Institut Pariwisata Trisakti, 2020)
This research aims to community movements both spontaneously and in an organized manner, such as the Trash Hero Indonesia community and other community activities that care about the high waste generation. In addition to the Trash Hero community, in-depth interviews were conducted with the Waste Bank and tourist attraction in knowing the management of waste generation. It is hoped that alternative activities will be obtained to help reduce the generation of plastic waste that supports the implementation of Bali Governor Regulation number 97 of 2018. Activities from the community are expected to be able to maintain and provide a positive legacy for future generations. The purpose of this research is to find movements made by the community to help reduce the generation of plastic waste on the island of Bali. The results of this study are expected to increase public awareness of waste management both organic and non organic. Keywords : Waste; Plastic; Tourism Image